Efektivitas Program Bimbingan Kerja dalam Mengembangkan Life Skill Warga Binaan Penjara - Pratama, Enggi; Fauzi, Ahmad (Journal of Nonformal Education and Community Empowerment, 2018)
The BIMKER program is one of the life skill WBP improvement activities in Class II A Prison Serang. This activity has been held for long time, but the effectiveness is not well-tested yet, this case is what made the researcher done the research. This research has purposes to know (1) The effectiveness of BIMKER program implementation in WBP life skill managing in Dr. Sahardjo Class II A Prison Serang-Banten. (2) personal skill, Social Skill, and vocational skill of WBP after participating in the BIMKER program in the Dr. Sahardjo Class II A Prison Serang-Banten.(3) supporting and demotivating factor in the BIMKER program of Dr. Sahardjo Class II A Prison Serang-Banten. The research methodology that used in this research is non experimental research which is have an intention to describe the result of the research because this kind of research is a research that observed variables for the real condition without any manipulation (intervention) of the researcher, and the research phenomenological is qualitative. In a research with qualitative phenomenological should based on data or information which is taken from the research: (1) Observation (2) Documentation, and (Interview) which is consist of: observation, registry, data and fact collection that happened with additional references from various resources such as book, journal and scientific article that related to discussed problem. The data collection technique and the data analysis in this research are data reduction, data presentation and verification or conclusion. From the research can taken conclusions: (1) the effectiveness of BIMKER program in managing WBP life skill in Dr. Sahardjo Class II A Prison Serang-Banten, the researcher summarize that the participant who participate the program already has knowledge, work experience, (life skill) and having an entrepreneur job in majority. (2) the personal skill, Social Skill, and vocational skill of WBP after participated in the BIMKER program Dr. Sahardjo Class II A Prison Serang-Banten, that WBP who participated in the BIMKER program already has personal capability competence, social capability and work capability. This factor is proven by training evaluation that done by a tutor after the training. (3) Supporting and demotivating factor in the BIMKER program in Dr. Sahardjo Class II A Prison Serang-Banten, that the supporting factor in the BIMKER program is more dominant rather than then demotivating factor itself, this information is proven by the outcome from the WBP.